Autologous chondrocyte implantation with Chondrosphere for treating articular cartilage defects in the knee: An evidence review group perspective of a NICE single technology appraisal - Armoiry, X; Cummins, E; Connock, M; Metcalfe, A; Royle, P; Johnston, R; Rodrigues, J; Waugh, N; Mistry, H (Springer, 2018)
Chondrosphere (Spherox) is a form of autologous chondrocyte implantation (ACI). It is licensed for repair of symptomatic articular cartilage defects of the femoral condyle and the patella of the knee with defect sizes up to 10 cm2 in adults. In a single technology appraisal (STA) [TA508] undertaken by the National Institute of Health and Care Excellence (NICE), Warwick Evidence was the Evidence Review Group (ERG) invited to independently review the evidence submitted by the manufacturer, Co.Don. The clinical effectiveness data came from their COWISI randomised controlled trial (RCT), which compared Chondrosphere with microfracture (MF). The timing of this appraisal was unfortunate given that MF was no longer the most relevant comparator because NICE had contemporaneously published guidance approving ACI in place of MF. Moreover, the COWISI RCT enrolled mostly patients with small defect sizes. Evidence of clinical effectiveness for Chondrosphere used in people with larger defect size came from another RCT, which compared three doses of Chondrosphere and that by design could not provide evidence comparing Chondrosphere to any other forms of ACI. To estimate the relative clinical performance of Chondrosphere versus other ACI, Co.Don conducted an indirect treatment comparison by network meta-analyses (NMA). The NMA was flawed in that the distribution of population characteristics that are effect modifiers greatly differed across the treatment comparisons of the network. The ERG questioned both the appropriateness of the NMA and the validity of the resulting estimates. Co.Don estimated the cost-effectiveness of Chondrosphere using a lifetime Markov model with all patients receiving the first repair during the first cycle of the model then moving into one of three health states: success, no further repair (NFR), or a second repair, if necessary. Subsequent to the first cycle, those who were a success either remained a success or moved to second repair. All those in NFR remained in NFR. The cost-effectiveness of Chondrosphere compared to other ACI forms relied on the clinical effectiveness estimates of success and failure rates obtained from the company’s indirect comparisons, the validity of which the ERG questioned. The company revised cost-effectiveness estimates for Chondrosphere versus MF and for Chondrosphere versus matrix-applied characterised autologous cultured chondrocyte implant (MACI) were £4360 and around £18,000 per quality-adjusted life year gained, respectively. NICE recommended ACI using Chondrosphere for treating symptomatic articular cartilage defects of the femoral condyle and patella of the knee in adults only if certain requirements were met.